Design of multi-modal obstruction to control tonal fan noise using modulation principles. (10th November 2015) - Gérard, Anthony; Moreau, Stéphane; Berry, Alain; Masson, Patrice
Abstract: The approach presented in this paper uses a combination of obstructions in the upstream flow of subsonic axial fans with B blades to destructively interfere with the primary tonal noise at the blade passage frequency. The first step of the proposed experimental method consists in identifying the independent radiation of B − 1 and B lobed obstructions at the control microphones. During this identification step, rotating obstructions allow for the frequencies of primary and secondary tonal noise to be slightly shifted in the spectrum due to modulation principles. The magnitude of the secondary tonal noise generated by each obstruction can be adjusted by varying the size of the lobes of the obstruction, and the phase of the secondary tonal noise is related to the angular position of the obstruction. The control obstructions are then optimized by combining the B − 1 and B lobed obstructions to significantly reduce the acoustic power at blade passage frequency.